Different cationic forms of (–)‐cytisine in the crystal structures of its simple inorganic salts. Issue 11 (24th October 2018) - Owczarzak, Agata; Przybył, Anna K.; Kubicki, Maciej
Abstract : The crystal structures of 13 simple salts of cytisine, an alkaloid isolated from the seeds of Laburnum anagyroides, have been determined. Cytisine has two potential protonation sites, i.e. the N atom of the piperidine ring and the carbonyl O atom of the pyridone ring. Three forms of the cytisinium cation were identified, namely the monocation, which is always protonated at the N atom, the dication, which utilizes both protonation sites, and the third form, which contains two cytisine moieties connected by very short and linear O…H…O hydrogen bonds. Abstract : The crystal structures of 13 simple salts of cytisine, an alkaloid isolated from the seeds of Laburnum anagyroides, have been determined, namely cytisinium (6‐oxo‐7, 11‐diazatricyclo[7.3.1.0 2, 7 ]trideca‐2, 4‐dien‐11‐ium) bromide, C11 H15 N2 O + ·Br −, cytisinium iodide, C11 H15 N2 O + ·I −, cytisinium perchlorate, C11 H15 N2 O + ·ClO4 −, cytisinium iodide triiodide, C11 H15 N2 O + ·I − ·I3 −, cytisinium chloride monohydrate, C11 H15 N2 O + ·Cl − ·H2 O, cytisinium iodide monohydrate, C11 H15 N2 O + ·I − ·H2 O, cytisinium nitrate monohydrate, C11 H15 N2 O + ·NO3 − ·H2 O, hydrogen dicytisinium tribromide, C22 H31 N4 O2 3+ ·3Br −, hydrogen dicytisinium triiodide, C22 H31 N4 O2 3+ ·3I −, hydrogen dicytisinium triiodide diiodide, C22 H31 N4 O2 3+ ·I3 − ·2I −, hydrogen dicytisinium bis(triiodide) iodide, C22 H31 N4 O2 3+ ·2I3 − ·I −, cytisinediium (6‐oxidaniumylidene‐7, 11‐diazatricyclo[7.3.1.0 2, 7 ]trideca‐2, 4‐dien‐11‐ium) bis(perchlorate), C11 H16 N2 O 2+ ·2ClO4 −, and cytisinediium dichloride trihydrate, C11 H16 N2 O 2+ ·2Cl − ·3H2 O. Cytisine has two potential protonation sites, i.e. the N atom of the piperidine ring and the carbonyl O atom of the pyridone ring. Three forms of the cytisinium cation were identified, namely the monocation, which is always protonated at the N atom, the dication, which utilizes both protonation sites, and the third form, which contains two cytisine moieties connected by very short and linear O…H…O hydrogen bonds, with an O…O distance of approximately 2.4 Å. This third form may therefore be regarded as a 3+ species, or sesqui‐cation, and is observed solely in the salts with bromide, iodide or triiodide (heavier halogen) anions. The cation is quite rigid and all 19 cytisinium fragments in the studied series have very similar conformations. The crystal structures are determined mainly by Coulombic interactions and hydrogen bonds, and the latter form is determined by different networks. Additionally, some anion–π and lone‐pair…π secondary interactions are identified in almost all of the crystal structures. Hirshfeld surface analysis generally confirms the role of different interactions in the determination of the crystal architecture.